Occupy Wall Street: Neo-Classical Social Movement of the 21st Century - Milan Radonjić (Političke Perspektive, 2014)
Joint effect of 2008 economic crises and continous world-wide present deficite of political legitimacy have in 2011 given birth to global resistance, but also facilitated development of its new strategies and tactics. Aldough we are still by large able to understand these contemporary models of collective action with help of New Social Movement Theory, today they objectivelly grasp a wider field of meaning, mainly for reason of their demands for radical transformation of both economic and political system. Contemporary social movements are still struggling for re-interpretation of meaning, and identity issues, but not any more for any particular goal. Instead, they seek systemic change. This extremelly important shift of strategic orientation, which makes new movements a bit old – that is classical, remains in our oppinion, undervalued both in academic, and general public for the reasons that we will try to comprehend, in this writing.